Investigating Orthorexia Nervosa With the ORTO-R in a Sample of University Students With or Without Subthreshold Autism Spectrum: Focus on Dietary Habits and Gender Differences - Dell'Osso, Liliana; Cremone, Ivan Mirko; Chiarantini, Ilaria; Arone, Alessandro; Casagrande, Danila; Massimetti, Gabriele; Carmassi, Claudia; Carpita, Barbara (Frontiers in Psychiatry, 2022)
Background: The aim of the present study was to investigate the presence of Orthorexia (ON) symptoms in a sample of University students with or without autistic traits (AT), specifically focusing on evaluating the role of gender and of dietary habits in the association between ON and autism spectrum. Methods: Subjects were requested to anonymously fill out the questionnaires through an online form. Results: 2140 students participated in the study. Subjects with significant AT, measured by means of the Adult Autism Sub-threshold spectrum (AdAS Spectrum) reported significantly higher ON symptoms, as measured by ORTO-R scores, than subjects with low AT. Females and subjects following a vegetarian/vegan diet reported significantly higher ORTO-R scores than males and than subjects following an omnivorous diet, respectively. Significant positive correlations were found between ORTO-R and AdAS Spectrum scores. A decision tree model, with gender, type of diet and presence of high AT as independent variables and ORTO-R score as dependent variable, showed in the first step the presence of significantly higher ORTO-R scores among females than among males, and in the second step showed in both genders the presence of higher ORTO-R scores among subjects with high AT than in those with low AT. A significant interaction of gender and presence/absence of high AT was reported on ORTO-R score, with a higher increasing trend of ORTO-R score with the increase of AdAS Spectrum score among females than among males. Conclusions: Our results further highlighted the association between AT and ON, in particular among females.